CHARACTERISTIC OF INDECOMPOSABLE REPRESENTATION OF FINITE QUIVER - SAPUTRA (20114011), BANYU
Let Q be a quiver. Its representation M=(M_x,M_α ) consist of family of vector spaces M_x indexed by vertices of Q together with a family of linear maps M_α indexed by the arrows of Q. Coefficient quiver of representation M can be constructed by the base B. In this tesis weÃ‚Â’ll see relation between indecomposable representation and its coefficient quiver. Moreover weÃ‚Â’ll see relation between simple M and its self extension Ext1KQ (M,M).